2018
DOI: 10.1139/cjfas-2017-0123
|View full text |Cite
|
Sign up to set email alerts
|

Can a square-mesh panel inserted in front of the cod end improve size and species selectivity in Mediterranean trawl fisheries?

Abstract: An experiment was conducted to assess the selectivity in a typical Mediterranean bottom trawl, equipped with a square-mesh panel inserted in front of the cod end, for Atlantic horse mackerel (Trachurus trachurus), European hake (Merluccius merluccius), red mullet (Mullus barbatus), poor cod (Trisopterus minutus), broadtail shortfin squid (Illex coindetii), and deep-water rose shrimp (Parapaeneus longirostris). The release efficiency of undersized individuals through the panel was low. The differences in select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Earlier studies by Alzorriz et al (2016) and Brčić et al (2016Brčić et al ( , 2018, which were carried out in the Atlantic Ocean and the Mediterranean Sea, respectively, showed that few individuals of hake escaped through SMPs located in front of the codend and on the top panel of the trawl. These low escape rates were attributed mainly to the low contact probability between the fish and the SMP, which resulted in few fish being sizeselected by the panel.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Earlier studies by Alzorriz et al (2016) and Brčić et al (2016Brčić et al ( , 2018, which were carried out in the Atlantic Ocean and the Mediterranean Sea, respectively, showed that few individuals of hake escaped through SMPs located in front of the codend and on the top panel of the trawl. These low escape rates were attributed mainly to the low contact probability between the fish and the SMP, which resulted in few fish being sizeselected by the panel.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, SMPs can be an alternative measure to increase the escape of some species without excessively affecting profitability (Brčić et al 2016). Several studies have investigated the functioning and release efficiency potential of SMPs, but the release efficiency of SMPs has often been estimated to be low due to the low probability of contact of the fish with the panel (Herrmann et al 2014, Alzorriz et al 2016, Brčić et al 2018. There have been attempts to improve the fishpanel contact probability by inserting stimulating devices in the gear.…”
Section: Introductionmentioning
confidence: 99%
“…1967. However, a recent study (Brčić et al, 2018) has predicted a high risk of retention of undersized individuals of several species with both mesh types, highlighting the need for additional measures, besides codend size selection, to improve the exploitation pattern of Mediterranean bottom trawls. Square-Mesh Panels (SMPs) are among the simplest technological measures that can be applied to bottom trawls when codend size selection alone does not prevent retention of undersized individuals.…”
Section: Introductionmentioning
confidence: 99%
“…The size selectivity data was analyzed using the software SELNET (Herrmann et al 2012;Brčić et al 2018aBrčić et al , 2018b. We assumed that the probability of each redfish being retained after entering the codend was independent of other fish and that the number of individuals of a specific length class remaining in the codend or the cover has a binominal distribution (i.e., length-dependent retention probability).…”
Section: Selectivity Data Analysismentioning
confidence: 99%